Incidence of atrial fibrillation in whites and African-Americans: the Atherosclerosis Risk in Communities (ARIC) Study - Alonso, Alvaro (2009)
OBJECTIVES: To define the incidence and cumulative risk of atrial fibrillation (AF) in a population-based cohort of whites and African-Americans. BACKGROUND: African-Americans reportedly have a lower risk of AF than whites despite their higher exposure to AF risk factors. However, precise estimates of AF incidence in African-Americans have not been previously published. METHODS: We studied the incidence of AF in the Atherosclerosis Risk in Communities Study, which has followed up 15,792 men and women aged 45-65 at baseline from four communities in the United States since 1987. AF cases were identified from ECGs conducted at baseline and three follow-up visits, and from hospitalizations and death certificates through the end of 2004. During follow-up, 1,085 new cases of AF were identified (196 in African-Americans, 889 in whites). RESULTS: Crude incidence rates of AF were 6.7, 4.0, 3.9 and 3.0 per 1,000 persons per year in white men, white women, African-American men and African-American women, respectively. Increasing age was exponentially associated with an elevated risk of AF. Compared to whites, African-Americans had a 41% (95% confidence interval: 8%-62%) lower age- and sex-adjusted risk of being diagnosed with AF. The cumulative risk of AF at age 80 was 21% in white men, 17% in white women, and 11% in African-American men and women. CONCLUSION: In this population-based cohort, African-Americans presented a lower risk of AF than whites. Still, the burden of AF among the former is substantial, with 1 in 9 receiving a diagnosis of AF before the age of 80.